An Atypical Case of Primary Angiitis of Central Nervous System Featuring Normal Cerebrospinal Fluid Analysis and Multiple Cavernomas - Salil Gundewar; Pravin Naphade; Satish Nirhale; Prajwal Rao; Pranit Khandait (Journal of Clinical and Diagnostic Research)
Primary Angiitis of Central Nervous System (PACNS) is a rare disease with an incidence of 2.4 cases per 10000 persons per year. Diagnosis of the condition is challenging due to its variable presentation. Delay in treatment may cause irreversible neurological consequences. Evaluation includes laboratory tests such as complete blood count, renal function tests, urine routine microscopy, Erythrocyte Sedimentation Rate (ESR), Anti-Nuclear Antibodies (ANA) by Immunofluorescence Assay (IFA) and blot method, complement (C3 and C4) levels, Cerebrospinal Fluid (CSF) evaluation and neuroimaging, including Magnetic Resonance Imaging (MRI) of the brain. Digital Subtraction Angiography (DSA) and High-Resolution Vessel Wall Imaging (HRVWI) may help establish the diagnosis. The Gold standard investigation for diagnosis of PANCS is histopathology of brain biopsy tissue. Here, a case of a 40-year-old male with acute and chronic infarcts in multiple territories with no prior co-morbid conditions is presented. CSF study was within normal limits. Although, DSA and HRVWI showed inflammation in the walls of the left Middle Cerebral Artery (MCA) (M2, M3 segment) and bilateral Anterior Cerebral Arteries (ACAs). This highlights the extremely rare association of PACNS with normal CSF analysis. Diagnosing PACNS is challenging due to its variable presentation, and CSF analysis is typically abnormal in 80-90% of cases. However, the CSF analysis was normal in this case, underscoring the importance of further evaluation in cases with a high suspicion of PACNS.